2022
DOI: 10.1002/glia.24220
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐beta signaling modulates perineurial glial bridging following peripheral spinal motor nerve injury in zebrafish

Abstract: Spinal motor nerves are necessary for organismal locomotion and survival.In zebrafish and most vertebrates, these peripheral nervous system structures are composed of bundles of axons that naturally regenerate following injury. However, the cellular and molecular mechanisms that mediate this process are still only partially understood. Perineurial glia, which form a component of the blood-nerve barrier, are necessary for the earliest regenerative steps by establishing a glial bridge across the injury site as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…More recently, it has been shown that inhibition of TGF-β signaling perturbs perineurial glia maturation, a cell type that ensheaths axon-Schwann cell bundles and forms the bloodnerve-barrier (Kucenas, 2015;Morris et al, 2017). Interestingly, another study from the same laboratory has shown that TGF-β signaling pathway, through its downstream mediator connective tissue growth factor-a (ctgfa), is involved in forming the bridge between proximal and distal stumps after motor nerve injury in zebrafish embryos (Arena et al, 2022). However, to date, there is no specific evidence demonstrating the role of TGFβ in ALS zebrafish models.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that inhibition of TGF-β signaling perturbs perineurial glia maturation, a cell type that ensheaths axon-Schwann cell bundles and forms the bloodnerve-barrier (Kucenas, 2015;Morris et al, 2017). Interestingly, another study from the same laboratory has shown that TGF-β signaling pathway, through its downstream mediator connective tissue growth factor-a (ctgfa), is involved in forming the bridge between proximal and distal stumps after motor nerve injury in zebrafish embryos (Arena et al, 2022). However, to date, there is no specific evidence demonstrating the role of TGFβ in ALS zebrafish models.…”
Section: Discussionmentioning
confidence: 99%